2023
DOI: 10.1002/chem.202300625
|View full text |Cite
|
Sign up to set email alerts
|

N‐Protonation as a Switch of the Twisted Excited States with ππ* or nπ* Character and Correlation with the π‐Electrons Characteristic of Rotatable Bonds

Abstract: N-protonation for numerous fluorophores is widely known as an efficient switch for the fluorescence turn-on/off in acidic conditions, which has been applied in various scenarios that involve pH monitoring. Yet the universal mechanism for fluorescence regulation through N-protonation is still elusive. Herein, the excited state deactivation processes are systematically investigated for a series of nitrogen-containing fluorescent probes through theoretical approaches. Two types of mechanisms for the complex fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…The proposed localized-orbital locator (LOL), chemically coded by Selvin and Savin, is beneficial to describe the major electronic concentrations on the surface of our studied compounds. It is preferable to demonstrate the location of free electrons on surfaces, which facilitates the charge transfer phenomena between chemical groups. Figure displays the M material, the Au–M–Au system with atomic numbering, and the 2D-LOL figures along the X - and Y -axes.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed localized-orbital locator (LOL), chemically coded by Selvin and Savin, is beneficial to describe the major electronic concentrations on the surface of our studied compounds. It is preferable to demonstrate the location of free electrons on surfaces, which facilitates the charge transfer phenomena between chemical groups. Figure displays the M material, the Au–M–Au system with atomic numbering, and the 2D-LOL figures along the X - and Y -axes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the absence of highly polar −C(�O)O − and −SO 3 − groups in the acidic medium reduced both dipole−dipole and hydrogen bonding interactions, decreasing the extent of π → π* transitions. 35 Ratiometric pH sensing and pK a determination: The ratiometric pH sensing ability of SGO nanoparticle incorporated HLEP3 was realized from the pH-dependent variation of I 528 /I 488 (R), i.e., ratios of maximum emission intensities at 528 nm to those at 488 nm. Here, R showed nonlinear variation within pH = 7.0−13.0 (Figure 6f), however, a linear change was noticed within pH = 8.0−11.0 (Figure 6g).…”
Section: Effect Of Solvent Polarity On the Emissions Of Sgo Nanoparti...mentioning
confidence: 99%
“…The differences in the extent of n → π* and π → π* transitions, hydrogen bonding and dipole−dipole interactions, and HOMO−LUMO energy gap are expected to be associated with the protonation and deprotonation of HLEPs. 17,35 Such conversion may result in the different emission wavelengths with pH variation, broadening the opportunity of ratiometric dynamic pH sensing ability of HLEPs. 17 − fluorophores have been developed from the preoptimized composition of purely aliphatic LEPs for dual sensing of Co(II) and Bi(III) at different wavelengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its wide applications, the sensing mechanism of pHrodo, especially its excited-state dynamics, is not yet well understood. A comprehensive understanding of its sensing mechanisms is beneficial for the further application and development of new fluorescent probes. , As shown in Figure , the chemical structure of pHrodo (determined by Ogawa and co-workers on the basis of mass spectroscopic analysis and 1 H and 13 C NMR) is similar to that of aminorhodamine (ARh), which shows a fluorescence off–on switch with a change in pH and can function as a fluorescent pH probe, as well. For ARh, a detailed study revealed their sensing mechanism can be well understood by a bichromophore model. In the bichromophore model, the lowest excited state [the first excited state (S 1 )] is formed by strong coupling between two chromphores and is a weakly transition-allowed charge transfer (CT) state, which can be excited from the ground state (S 0 ).…”
mentioning
confidence: 99%